The Implication of Farmers - Herders Conflicts on the Socio-Economic Development of Omala L.G.A, Kogi State, North Central Nigeria - Success Esomchi Obi; Sunny Odikpa; Edegbo Sunday Jeremiah; Abubakar Yakubu Emeje; Onuche Godwin (International Journal of Qualitative Research, 2021)
Famers’- Herders’ conflict has become a widespread occurrence spreading to all parts of Nigeria. The study examined how farmers-herdsmen conflict constitutes a threat to rural development, internal security, and socio-economic development in Nigeria about Omala Local Government Area of Kogi State, North Central Nigeria. The study adopted the qualitative method making use of semi-structured interviews and 100 informants were purposively selected. Findings from the study revealed among others that; Crop damage by cattle, land encroachment without permission, inadequate grazing reserves, lack of access to water points, killing of stray cattle, pollution of the water point, cattle routes blockage, Mbororo migrants, ECOWAS treaty, fertile land of the host community, socio-economic, cultural differences, the political economy of cattle herders were major causes and persistence of farmers-pastoralists conflicts. The study among others recommends that; since farmers-pastoralists conflicts were resource-based conflict due to blockage of cattle route by farmers which eventually leads to encroachment of farmers land and thus translate to open violence and animosity, there is a need for resignification of cattle routes for the pastoralist to have a route to avoid farmlands encroachment, regarding the transit route for irregular migrants through Niger, Senegal, Mali, Ivory Coast, Chad, Cameroon, it is suggested that the Minister of Interior should initiate dialogue with the neighboring governments on how to address and curb the rising number of migrants transiting border Nations. Based on the study findings, to end this crisis once and for all, there is a need for the consideration of cattle colonies implementation while implementing former recommendations.